Comparison of gravimetric and mantle flow solutions for sub-lithopsheric stress modeling and their combination. Issue 2 (31st January 2018) - Eshagh, Mehdi; Steinberger, Bernhard; Tenzer, Robert; Tassara, Andrés
Summary: Based on Hager and O'Connell's solution to mantle flow equations, the stresses induced by mantle convection are determined using the density and viscosity structure in addition to topographic data and a plate velocity model. The solution to mantle flow equations requires the knowledge of mantle properties that are typically retrieved from seismic information. Large parts of the world are, however, not yet covered sufficiently by seismic surveys. An alternative method of modeling the stress field was introduced by Runcorn. He formulated a direct relation between the stress field and gravity data, while adopting several assumptions, particularly disregarding the toroidal mantle flow component and mantle viscosity variations. A possible way to overcome theoretical deficiencies of Runcorn's theory as well as some practical limitations of applying Hager and O'Connell's theory (in the absence of seismic data) is to combine these two methods. In this study, we apply a least-squares analysis to combine these two methods based on the gravity data inversion constraint on mantle flow equations. In particular, we use vertical gravity gradients from the Gravity field and steady state Ocean Circulation Explorer that are corrected for the gravitational contribution of crustal density heterogeneities prior to applying a localized gravity-gradient inversion. This gravitational contribution is estimated based on combining the Vening Meinesz-Moritz and flexural isostatic theories. Moreover, we treat the non-isostatic effect implicitly by applying a band-limited kernel of the integral equation during the inversion. In numerical studies of modeling, the stress field within the South American continental lithosphere we compare the results obtained after applying Runcorn and Hager and O'Connell's methods as well as their combination. The results show that, according to Hager and O'Connell's (mantle flow) solution, the maximum stress intensity is inferred under the northern Andes. Additional large stress anomalies are detected along the central and southern Andes, while stresses under most of old, stable cratonic formations are much less pronounced or absent. A prevailing stress-vector orientation realistically resembles a convergent mantle flow and downward currents under continental basins that separate Andean Orogeny from the Amazonian Shield and adjacent cratons. Runcorn's (gravimetric) solution, on the other hand, reflects a tectonic response of the lithosphere to mantle flow, with the maximum stress intensity detected along the subduction zone between the Nazca and Altiplano plates and along the convergent tectonic margin between the Altiplano and South American plates. The results also reveal a very close agreement between the results obtained from the combined and Hager and O'Connell's solutions.